Temporal changes in chemical properties of acid soil profiles treated with magnesium limestone and gypsum - Jusop, Shamsuddin; Sharifuddin, H. A. H.; Ishak, Che Fauziah; Edwards, D. G.; Bell, L. C. (Universiti Putra Malaysia, 2010)
Effects of ground magnesium limestone (GML) and gypsum on the properties of Ultisols at two sites, involving a corn groundnut rotation, were studied over 24 months. GML or gypsum was incorporated into the soils of the Bungor and Rengam Series (Typic Paleudults), at the rates of 0, 0.5, 1.0, 2.0, 4.0, and 8.0 t ha-1 to depths of 15 cm (GML and gypsum) and 30 cm (GML). Increases in soil pH and exchangeable Ca and Mg arising from GML application were confined mainly to the zone of incorporation. However, there was a decrease of exchangeable Al at deeper depths. After 15 months, there was a tendency for the pH and exchangeable Ca and Mg on the zone of incorporation to decrease and for the exchangeable Al to increase, effects being the least at the high rates of GML application. There was no significant change in pH or exchangeable Al as a result of gypsum application, but there were increases in exchangeable Ca and extractable SO4²- in both the zone of incorporation and the subsoil. With time, the exchangeable Ca and extractable SO4²- in the sub-soils were found to increase, but their concentration in the zone of incorporation decreased. The pH of the soil solution of the control treatment was about 4.0, while Al and Mn concentrations were 150 and 50 µM, respectively. At the GML rate of 2.0 t ha-1 or less, Al in the soil solution was found to exist in the inorganic monomeric form. Meanwhile, the GML application at the rates > 4 t ha-1 could have resulted in complexation of some of Al. In particular, Al3+ was the dominant Al species at low pH and liming resulted in a decrease of Al3+ species and increase of hydroxyl-Al monomers. GML needed to raise the pH of the soil solution to about 5 was 2.0 t ha-1; this consequently decreased Al and Mn concentrations to a low level. The application of gypsum resulted in a decrease and an increase of Al3+ and AlSO4+ activities, respectively.